Analysis of User Experience on the MyPertamina Application using User Experience Questionnaire Method - Ramadhan, Muhammad Gilang; Oktadini, Nabila Rizky; Putra, Pacu; Sevtiyuni, Putri Eka; Meiriza, Allsela (Jurnal Komtika (Komputasi dan Informatika), 2023)
MyPertamina is an application launched by PT Pertamina (Persero) in 2017. Although the MyPertamina application has many programs that should be able to facilitate the community but unfortunately the rating of this application is still bad, namely 3.3 on a scale of 5 on Google PlayStore from hundreds of thousands of user reviews both android and ios this application has negative reviews. Thus user experience (UX) analysis is needed. User Experience Questionnaire (UEQ) is the right method in this research. Because this method interacts directly with what users feel when operating the MyPertamina application. There are 6 variables namely attractiveness, stimulation, and novelty that have a value (above average) except perspicuity and dependability (below average), and there is an average scale of three aspects and a value of Pragmatic Quality 1.11 (positive), Hedonic Quality 0.93 (positive), and Attractiveness 1.21 (positive).